Computer Simulation of Thermal Cycling of Porous Coatings: Hybrid Excitable Cellular Automata Method; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Moiseenko D. D.; Panin S. V. Sergey Viktorovich; Maksimov P. V.; Panin V. E. Viktor Evgenyevich; Babich D. S.; Schmauder S. (2018, 2018)
Title screen